Spatiotemporal Analysis of LST and UHI Dynamics of Delhi NCR over 25 years (2000-2024) using GEE - Malik, Abhishek; Mor, Shubham; Singh, Ranbir; Kalotra, Gaurav (International Journal of Aquatic Research and Environmental Studies, 2026)
Urbanization in the National Capital Region (NCR) of India over the past 25 years (2000 – 2024) has drastically changed the energy balance of the surface of the land. This report presents a comprehensive longitudinal study of land surface temperature, diurnal temperature range, and urban heat island for all 35 districts in the NCR and utilizes MODIS thermal data (MOD11A2) and MODIS land cover data (MCD12Q1) that have been processed using Google Earth Engine and a dynamic rural masking method to quantify the real intensity of urban heat islands. Spatial analysis of the thresholds shows a significant growth in impervious surfaces caused by anthropogenic activity to be the main contributor to thermal anomalies in NCR. A major diurnal inversion exists between the urban cores (which exhibit the Urban Cool Island [UCI] effect) on summer days, resulting from rapid thermal heating of surrounding semi-arid barren land. The true environmental issue is found after sunset, when the high thermal inertia and summer heat retained within the urban matrix create extreme Nighttime Urban Heat Island (NUHI) impacts and a significant reduction in the diurnal temperature range (DTR) due to inhibited nocturnal cooling (overnight). Finally, the use of Pearson correlation analysis using 2011 Census demographic information has identified a significant positive correlation (r = 0.76) between population density and NUHI intensities and identified anthropogenic clustering as the primary cause of thermal stress caused by population density.